ANALISIS PROSES REKRUTMEN PEKERJA MIGRAN INDONESIA PADA PT AKADEMI INDONESIA CERDAS (GAPAI.ID) MAMPANG PRAPATAN JAKARTA SELATAN - Lilis Anastasya Siringoringo; Moh. Jazuli (Journal of Research and Publication Innovation, 2025)
Labor growth is faster than absorption. Because the increasing number of unemployed people shows that a solution must be immediately found for the workforce problem so that there is no increase in the number of unemployed people in Indonesia. Working abroad or becoming a migrant worker abroad is the desire of most Indonesians. This research aims to analyze the recruitment process of Indonesian migrant workers at PT Akademi Indonesia Cerdas (Gapai.id). This research is a qualitative descriptive research approach, namely a research method used to examine the condition of natural objects, where the researcher is the key instrument. Data collection procedures were carried out using observation, interviews and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. From the research results, PT Akademi Indonesia Cerdas (Gapai.id) is one that uses the benefits of special technological developments in the recruitment process for working abroad and is the right solution for job information seekers. Online recruitment sources such as Instagram advertisements, the Gapai.id website, Glints, Indeed, KUPU, REDY Indonesia are one of the main strategies to reach Indonesian migrant workers widely and non-online sources such as Job fairs used by PT Akademi Indonesia Cerdas can be a strong basis and quite effective in supporting the development of the e-recruitment process. The registration process for filling out the pre-screening form has been carried out well as the first step for PT Akademi Indonesia Cerdas (Gapai.id) to recruit Indonesian migrant workers who meet the qualifications. However, during the interviews, several obstacles were still found in the assessment stages of Indonesian migrant workers, such as the ability to communicate in English, an important requirement for working abroad and the ability to afford the costs, which caused Indonesian migrant workers to withdraw from the recruitment process. After the interview is successful in finding suitable Indonesian migrant workers, the administration procedures of Indonesian migrant workers must be carried out as regulated in Law of the Republic of Indonesia Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. Similar to what is clearly stated in Government Regulation (PP) Number 10 of 2020 concerning Procedures for the Placement of Indonesian Migrant Workers by the Indonesian Migrant Worker Protection Agency (BP2MI). Overall, the recruitment process has complied with the regulations set because PT Akademi Indonesia Cerdas (Gapai.id) is collaborating with the Indonesian Migrant Worker Placement Company (P3MI) legally, although more efforts are needed to increase transparency and protection for Indonesian migrant workers abroad.